The relationship between individual employee motivation and performance within Eskom - Majikijela, Nondzuzo (University of the Free State, 2018)
The modern business environment is increasingly becoming more dynamic and unpredictable, and organisations need to keep their individual employees motivated in performing their day to day activities in order to achieve their desired outcomes. Motivation and performance are considered to have a direct relationship and under these circumstances managers are compelled to ensure the balance between motivation and performance. According to Ferreira (2017), organisations are interested in the topic of motivation, because it increases performance and employees that are motivated impacts positively on customers, which significantly contributes to organisational success. Keeping employees motivated helps the leadership of the organisation to make the managing of people to be much easier, which in turn will contribute to the success or failure of the organisation. Employee diversity has the ability to increase performance and produce quality products (Cheruvelil, Soronno, Weathers, Hanson, Goring, Filstrup & Read 2014). Maslow (1970) conducted a study that assessed the individual levels of motivation. According to Datta (2013) in formulating of positive theory of motivation Maslow started with physiological needs in the hierarchy of needs, once the physiological needs have been satisfied other needs such as safety, belongingness, love and esteem emerge. It is considered that most of basic needs are psychological. It is difficult to try to motivate an individual who does not have food and shelter. According to Band, Shah and Sriram (2016), the following questions need to be asked with regards to promoting motivation within an organisation: Whether employees require high salaries, job security, or opportunities for growth and development, or safe working environment. The research study will focus on Eskom Northern Cape Operating Unit (NCOU), which is a unit within Eskom. Eskom is a South African electricity public utility; the company was established in 1923 under the name the Electricity Supply Commission (ESC) by the government of the Union of South Africa in terms of the Electricity Act (1922). The company was also called by its Afrikaans name known as Elektrisiteits-voorsieningskommissie (EVKOM). The two acronyms of ESCOM and EVKOM were combined in 1986 to the company name ESKOM. It is wholly owned by the South African government. Eskom is one of the top 20 utilities in the world by generation capacity (net maximum self-generated capacity: 41 194MW). Eskom has 3 line functions that enable the organisation to achieve its overall vision and objectives, which are: Generation, Transmission and Distribution. Furthermore Transmission and Distribution are divided into 9 Operating Units (OU's) which are based in provinces.
Dissertation (MBA (Business Administration))--University of the Free State, 2018